Implementation of the STAD-Type Cooperative Learning Model to Improve Student Learning Outcomes - Mhd. Zulfhadli (Global Education Journal, 2025)
Education plays a fundamental role in shaping human resources that are of high quality, have strong character, and are adaptive to global challenges. However, the learning process in madrasah ibtidaiyah is still dominated by conventional teacher-centered methods, which affects students' low learning outcomes. This study aims to determine the effectiveness of implementing the Student Teams Achievement Division (STAD) cooperative learning model in improving student learning outcomes at MIN 3 Aceh Tenggara. The study uses a quantitative approach with a quasi-experimental design of the Nonequivalent Control Group Design type, involving two classes, namely an experimental class and a control class, each consisting of 25 students. Research instruments include learning outcome tests, student activity observation sheets, and documentation. Data analysis was conducted descriptively and inferentially using the Independent Sample t-test. The results of the study showed a significant increase in learning outcomes in the experimental class with a post-test average score of 83.6 compared to the control class at 72.1 (t_calculated = 5.62 > t_table = 2.01; p < 0.05). In addition, student learning activity increased from the category of "moderately active" to "very active" by the end of the sessions. The implementation of the STAD model not only improved cognitive learning outcomes but also developed social skills such as cooperation, responsibility, and communication. These findings confirm that the STAD model is relevant to the principles of the Independent Curriculum and can be considered an effective alternative for creating active, collaborative, and meaningful learning in elementary school madrasahs.